Management Strategy in Improving Company Performance - Syamsuddin, Syamsuddin; Aisyah, Sitti; Hasanah, Uswatun; Sundari, Sri (Formosa Journal of Multidisciplinary Research, 2024)
Strategic management plays an important role in improving company performance by setting clear goals, conducting environmental analysis with SWOT analysis, making proper decisions, implementing plans effectively, evaluating and measuring performance, developing competitive advantages, and creating an organizational culture that is result-oriented. This study focuses on strategic management in improving company performance through literature study from previous research references that are relevant to the topic of study. The results obtained by integrating aspects of management accounting and strategic management can significantly improve company performance for the short, medium, or long term.